OsFKBP20‐1b interacts with the splicing factor OsSR45 and participates in the environmental stress response at the post‐transcriptional level in rice. (13th February 2020) - Park, Hyun J.; You, Young N.; Lee, Areum; Jung, Haemyeong; Jo, Seung H.; Oh, Nuri; Kim, Hyun‐Soon; Lee, Hyo‐Jun; Kim, Ju‐Kon; Kim, Youn S.; Jung, Choonkyun; Cho, Hye S.
Summary: Sessile plants have evolved distinct mechanisms to respond and adapt to adverse environmental conditions through diverse mechanisms including RNA processing. While the role of RNA processing in the stress response is well understood for Arabidopsis thaliana, limited information is available for rice ( Oryza sativa ). Here, we show that OsFKBP20‐1b, belonging to the immunophilin family, interacts with the splicing factor OsSR45 in both nuclear speckles and cytoplasmic foci, and plays an essential role in post‐transcriptional regulation of abiotic stress response. The expression of OsFKBP20‐1b was highly upregulated under various abiotic stresses. Moreover genetic analysis revealed that OsFKBP20‐1b positively affected transcription and pre‐mRNA splicing of stress‐responsive genes under abiotic stress conditions. In osfkbp20‐1b loss‐of‐function mutants, the expression of stress‐responsive genes was downregulated, while that of their splicing variants was increased. Conversely, in plants overexpressing OsFKBP20‐1b, the expression of the same stress‐responsive genes was strikingly upregulated under abiotic stress. In vivo experiments demonstrated that OsFKBP20‐1b directly maintains protein stability of OsSR45 splicing factor. Furthermore, we found that the plant‐specific OsFKBP20‐1b gene has uniquely evolved as a paralogue only in some Poaceae species. Together, our findings suggest that OsFKBP20‐1b‐mediated RNA processing contributes to stress adaptation in rice. Significance Statement: We identified a new regulator of RNA processing in rice that enables adaptation to adverse environmental conditions. OsFKBP20‐1b, interacts with the splicing factor OsSR45 in both nuclear speckles and cytoplasmic foci, and facilitates the adaptation of rice plants to environmental stress. OsFKBP20‐1b functions in post‐transcriptional processing of mRNAs during export from the nucleus to cytoplasm Based on our data, we propose that, under normal conditions, OsFKBP20‐1b is weakly expressed and detected in a small number of nuclear speckles and cytoplasmic foci. However, when plants are exposed to various abiotic stresses, OsFKBP20‐1b expression is dramatically increased. In addition, OsFKBP20‐1b interacts with SR45, a splicing factor, in both nuclear speckles and cytoplasmic foci, suggesting that OsFKBP20‐1b plays a pivotal role in mRNA processing under abiotic stress conditions.